Satisfacción y desempeño laboral en una entidad estatal: caso personal de Migraciones Perú - Carrasco Pastor, Diego (2025)
The general objective of this study is to analyze the relationship between job satisfaction and job performance among Migration personnel at Jorge Chávez International Airport. This is an applied research study with a quantitative approach, a non-experimental, cross-sectional, and bivariate correlational design. The population consisted of 183 public servants. The sample obtained was from 125 people, who were surveyed using a questionnaire. According to Cronbach's alpha method, the reliability level for the variables job satisfaction (0.859) and job performance (0.790) is adequate, which guarantees the reliability of the instrument. The results indicate a positive and very strong correlation between job satisfaction and performance (Spearman's Rho correlation coefficient = 0.780). Results also indicate a positive and considerable correlation between the dimensions motivational factors (Spearman's Rho = 0.703) and hygiene factors (Spearman's Rho = 0.672) with job performance. Finally, the findings reveal predominantly medium and, in some cases, low levels in the variables and dimensions assessed. Therefore, the organization is recommended to delve deeper into these aspects and manage them strategically.